Sound velocities and thermal properties of BeX (X=S, Se and Te) alkaline-earth chalcogenides - Daoud, Salah (International Journal of Scientific World, 2016)
The sound velocities and some thermal properties of BeX (X=S, Se and Te) beryllium-chalcogenides large band gaps semiconductors have been estimated by employing some usual theoretical and emperical formulas. The lattice parameters and the elastic stiffness constants used here are taken from the literature. The longitudinal, transverse and average elastic wave velocities, the Debye temperature, the melting temperature, the thermal conductivity and the Grüneisen parameter are successfully predicted and analyzed in comparison with the available experimental and theoretical data. In general, our obtained results of these quantities agree well with the experimental and other theoretical data of the literature.